A numerical approach for femtosecond laser-induced photoionization in solids and its application. (7th June 2019) - Deng, Hongxiang; Guo, Wenli; Gao, Huanhuan; Li, Li; Yuan, Xiaodong; Zheng, Wanguo; Zu, Xiaotao
Abstract: Keldysh's analytical formula is a standard tool to calculate photoionization rate of a solid under intense laser radiation and widely used in application aspects of femtosecond laser. However, to obtain an analytic expression, some assumptions (or called approximations) are employed in the formula. In this work, a numerical approach is presented to calculate the photoionization rate of a solid under intense laser radiation. In present numerical approach, the assumptions which are employed in Keldysh's analytic formula are no longer needed. We find that numerical results are in a good agreement with Keldysh's analytical formula as laser intensity is not very high where interaction between laser radiation and solid in multi-photon regime, but quite different at high intensity where interaction is in tunneling regime. We find that the obvious difference at high intensity is originated from the small quasi momentum assumption employed in Keldysh's analytical formula. The small quasi momentum assumption is a good approximation in multi-photon regime, but not well satisfied in tunneling regime. Application to intense laser induced multi-photon absorption of GaAs shows that present numerical approach agrees with experiment much better.